Three Dimension Movie for the Students Ability in Narrative Writing - Fita Faridah (Reforma : Jurnal Pendidikan dan Pembelajaran, 2016)
This present study is conducted in order to improve the students’ writing narrative text by  using Three  Dimension  Movie.  It  has  several  steps  the  first  is  Pre-writing  In  this  phase  the  teacher combined  with  writing  process  included:  planning  and  drafting.  The  second  is  Whilst-  writing activities, in this phase the teacher combined with writing process include: revising and editing and  the  third  is  Post-writing  activities,  post-writing  tasks  allow  for  reflection,  sharing,  or publishing of the final product. This study employed Classroom Action Research (CAR) as the research  design.  The  procedure  of  the  research  involved  four  stages:  planning  the  action, implementing, observing, and reflecting. Using three dimension movie is intended the students deep understood the story of movie.Keywords: writing narrative text, three demension movie, and classroom action research